(untitled) (Web of Technology: Multidimensional Research Journal, 2024)
This article presents an evaluation of network-based dynamic modeling methods for AC power electronic systems. The evaluation encompasses key aspects including accuracy, generalization, robustness, computational efficiency, implementation considerations, and comparison with existing methods. Network-based models are assessed for their ability to accurately capture the dynamic behavior of AC power electronic systems under various operating conditions and to generalize to unseen data. Robustness against uncertainties and noise in the input data is also investigated. Computational efficiency and practical implementation considerations are evaluated, along with a comparison with traditional modeling approaches. The findings provide valuable insights into the suitability of network-based dynamic modeling methods for AC power electronic systems and their potential for practical application in industry.